A cross-sectional study to evaluate teaching skills of postgraduate medical students using component skill approach in microteaching - Swati R Deshpande; Shruti Shastri (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Microteaching is a teacher training technique where a teachers get a constructive feedback from peer or faculty in order to improve their teaching skills. Microteaching is conducted at the departmental level. By evaluating the components of microteaching, better teaching skills can be developed in postgraduate (PG) students. OBJECTIVES: The objectives of this study were to determine the pattern of teaching skills and to evaluate the components of teaching skills of microteaching in PG students. MATERIALS AND METHODS: It was a retrospective record-based study done over a period of 1 month. Microteaching assessment records of 34 PG students of the department of community medicine were analyzed. RESULTS: Teaching skills including setting induction during the class, lesson planning, presentation, and use of audio-visual aids were found to be satisfactory. Students lacked the skills of interaction and summarization of the topic. CONCLUSION: PG students' performance with many components was satisfactory, but still, there is a scope for improvement. Internalization of microteaching skills can make doctors a better teacher, a better learner, and a better health educator.